Policy Duration Effect under Zero Interest Rates: An Application of Wavelet Analysis - Kunio Okina; Shigenori Shiratsuka (Center for Economic Studies and ifo Institute (CESifo), 2004)
A major feature of recent monetary policy in Japan has been heavy reliance on the so-called policy duration effect. This policy employs a commitment to compensate for the central bank's inability to lower the interest rate below zero by altering the anticipated course of monetary policy actions. This paper analyzes the behavior of the yield curve and examines the effectiveness and limitations of monetary policy commitment under zero interest rates with four indicators for policy duration effect. Specifically, we extend our previous study (Okina and Shiratsuka (2003)) by applying wavelet analysis to indicators for policy duration effect. As in the previous study, the policy duration effect was found to be highly effective in stabilizing market expectations for the path of short-term interest rates, thereby reducing longer-term interest rates and flattening the yield curve. The policy duration effect, however, failed to reverse deflationary expectations in financial markets.
Keywords: 330; zero interest rate policy; quantitative monetary easing; policy duration effects; policy commitment; wavelet analysis